Pengajaran Kritik Seni Kontemporer melalui Pendekatan Semiotika - Sumarwahyudi Sumarwahyudi (Jurnal Pendidikan dan Penciptaan Seni, 2021)
This article is about teaching art criticism in college. Nowadays, the use of approaches that are not conventional, or only using a formalistic approach, is starting to bloom. This is because to discuss contemporary artworks that discourse increasingly diverse contemporary ideas, it is even more difficult to interpret them as an alternative to using a semiotic approach. One of them refers to the thought of Umberto Eco. One theory that can be used is called the "Theory of Lies." This theory is an interesting approach to interpreting signs in the subject of contemporary art criticism. In the use of this theory, a systematic approach is required, and application is based on semiotic principles. This is an effort to provide insight to students at the College of Arts in understanding the emergence of contemporary art works that are multi-interpretative, multi-interpretative, and subjective in nature.